The physical behavior of stabilised soft clay by electrokinetic stabilisation technology - Azhar, A. T. S.; Nordin, N. S.; Azmi, M. A. M.; Embong, Z.; Sunar, N.M.; Hazreek, Z. A. M.; Aziman, M. (2018)
Electrokinetic Stabilisation (EKS) technology is the combination processes of electroosmosis and chemical grouting. This technique is most effective in silty and clayey soils where the hydraulic conductivity is very low. Stabilising agents will assist the EKS treatment by inducing it into soil under direct current. The movement of stabilising agents into soil is governed by the principle of electrokinetics. The aim of this study is to evaluate the physical behavior of soft soil using the EKS technology as an effective method to strengthen soft clay soils with calcium chloride (CaCl2) as the stabilising agent. Stainless steel plates were used as the electrodes, while 1.0 mol/l of CaCl2 was used as the electrolyte that fed at the anode compartment. Soft marine clay at Universiti Tun Hussein Onn Malaysia was used as the soil sample. The EKS treatment was developed at Research Centre for Soft Soil (RECESS), UTHM with a constant voltage gradient (50 V/m) in 21 days. The result shows that the shear strength of treated soil was increased across the soil sample. The treated soil near the cathode showed the highest value of shear strength (24.5 – 33 kPa) compared with the anode and in the middle of the soil sample.